2017
DOI: 10.1002/ece3.3048
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the relative contribution of inter‐ and intrapopulation functional variability in wild populations of a tadpole species

Abstract: Functional traits are increasingly recognized as an integrative approach by ecologists to quantify a key facet of biodiversity. And these traits are primarily expressed as species means in previous studies, based on the assumption that the effects of intraspecific variability can be overridden by interspecific variability when studying functional ecology at the community level. However, given that intraspecific variability could also have important effects on community dynamics and ecosystem functioning, empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 76 publications
1
20
1
Order By: Relevance
“…Tadpoles from a single species can adapt to the availability of microhabitats or to local conditions (e.g., canopy cover, predation pressure, density‐dependence, Strauβ et al, ), which means ITV could be locally high for traits related to their position in the water column (body shape) or to the use of different resource types (Eterovick & Fernandes, ; Kopp & Eterovick, ). However, this contrasts with the findings of Zhao et al (), who found traits to be also widely variable among populations for a given species.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Tadpoles from a single species can adapt to the availability of microhabitats or to local conditions (e.g., canopy cover, predation pressure, density‐dependence, Strauβ et al, ), which means ITV could be locally high for traits related to their position in the water column (body shape) or to the use of different resource types (Eterovick & Fernandes, ; Kopp & Eterovick, ). However, this contrasts with the findings of Zhao et al (), who found traits to be also widely variable among populations for a given species.…”
Section: Discussioncontrasting
confidence: 99%
“…This variability was not simply driven by ontogeny, because all the stages presented similar variability in the different traits (Supporting information Figure S2). This is in agreement with the literature on tadpoles, which suggests that morphological characters are highly variable within species because anuran larvae are highly adaptive to their environment (Grosjean, 2005 Baldo et al, 2014), and even single species (Zhao et al, 2017). Interestingly, our results are overall in agreement with decompositions of trait variation performed in plants, as most studies have found between 25% and 33% of trait variation to occur within species (Albert et al, 2010;Messier et al, 2010;Siefert et al, 2015).…”
Section: Tadpole Traits Variability Within Speciessupporting
confidence: 93%
See 2 more Smart Citations
“…It has been demonstrated that ITV for several groups of organisms across different environmental gradients is high -e.g. trees, Jung et al (2010), Fajardo and Siefert (2018); invertebrates, Rudolf and Rasmussen (2013) , Dahirel et al (2017); and tadpoles, Zhao et al (2017), Jordani et al (2019) -strongly contributing to the increase of alpha and beta diversities (e.g. Spasojevic et al, 2016).…”
Section: Introductionmentioning
confidence: 99%